2016
DOI: 10.3389/fpls.2016.01932
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Myosins XI1, XI2, and XIK Are Crucial for Gravity-Induced Bending of Inflorescence Stems

Abstract: Myosins and actin filaments in the actomyosin system act in concert in regulating cell structure and dynamics and are also assumed to contribute to plant gravitropic response. To investigate the role of the actomyosin system in the inflorescence stem gravitropism, we used single and multiple mutants affecting each of the 17 Arabidopsis myosins of class VIII and XI. We show that class XI but not class VIII myosins are required for stem gravitropism. Simultaneous loss of function of myosins XI1, XI2, and XIK lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 64 publications
(129 reference statements)
1
30
0
Order By: Relevance
“…While it has been shown that myosin VIII also localizes to the cortical division site prior to mitosis (Wu and Bezanilla, 2014) and to the cell plate region during cytokinesis (Van Damme et al, 2004), no clear defect in plant growth was detected in quadruple knockouts in Arabidopsis that had lost all their myosin VIII genes (Talts et al, 2016). This lack of an apparent mutant phenotype contrasts with the clear morphological defects resulting from global myosin VIII loss in P. patens (Wu et al, 2011;Wu and Bezanilla, 2014).…”
Section: Slow Myosins May Function More As Tensors Than As Motorsmentioning
confidence: 95%
See 3 more Smart Citations
“…While it has been shown that myosin VIII also localizes to the cortical division site prior to mitosis (Wu and Bezanilla, 2014) and to the cell plate region during cytokinesis (Van Damme et al, 2004), no clear defect in plant growth was detected in quadruple knockouts in Arabidopsis that had lost all their myosin VIII genes (Talts et al, 2016). This lack of an apparent mutant phenotype contrasts with the clear morphological defects resulting from global myosin VIII loss in P. patens (Wu et al, 2011;Wu and Bezanilla, 2014).…”
Section: Slow Myosins May Function More As Tensors Than As Motorsmentioning
confidence: 95%
“…Specifically, the loss of Myo11B2, Myo11E, and Myo11F resulted in plants that had reduced stem growth rates, and these stems were stiffer and bent more slowly during gravistimulation (Talts et al, 2016). Interestingly, however, the sedimentation of amyloplasts was slower in the triple mutants (Talts et al, 2016), suggesting that their reduced gravitropism cannot be ascribed solely to slower growth.…”
Section: Myosin Motors Function Mostly Redundantly In a Variety Of Grmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model, the myosin XI-MyoB compartments represent a specialized transport system that drives streaming, rather than directly engaging individual organelles and secretory vesicles, which in turn delivers organelles and other types of vesicles to their destinations throughout the cell (14). Furthermore, existing genetic evidence indicates that cytoplasmic streaming is required for both polarized and diffuse cell growth because: (i) inactivation of myosins alone results in reduced cell elongation and expansion and affects plant growth and morphogenesis (15)(16)(17)(18)(19)(20); (ii) simultaneous inactivation of myosins and MyoBs results in synergistic phenotypes (13,14); and (iii) reduction in streaming velocity reduces plant growth, whereas increased velocity boosts that growth (21).…”
Section: Transport Of Myosin Cargoes In Plant Cellsmentioning
confidence: 99%